Mediation Analysis of Perceived Performance of Ghana Black Stars at the Qatar FIFA World Cup on Satisfaction of Football Fans: A Comparative Path Analysis - Appiah Kusi, Frank; Adedia, David; Atuwo-Ampoh, Vivian Della; Asosega, Killian (Indonesian Journal of Sport Management, 2024)
The mediation effects of the perceived performance of the Ghana Black Stars at the Qatar FIFA World Cup were examined on the satisfaction of football fans in Ghana. A cross-sectional design with closed-ended questions on Google Forms was used to collect data through football fans’ pages on WhatsApp and Facebook. Ghanaian adults aged 18 and above participated in the study with a sample of 618 gathered through a random sampling procedure. Estimators of Path models were compared with WLSMV outperforming others. The findings revealed that lack of coherence (p-value=0.002) among players reduces the performance of players, while the higher the perception of call-ups (p-value=0.035) the higher the perceived performance of Black Stars. Good perceived football governance (p-value<0.001) led to improvement in the perceived performance of the Black Stars. The higher performance of the Black Stars led to improved satisfaction among football fans (p-value<0.001). However, a poor technical team (p-value=0.015) for the Black Stars reduced the satisfaction of football fans. Lack of coherence among players (p-value=0.003) indirectly affects the satisfaction of football fans by compromising the perceived performance of Black Stars. Good governance (p-value=0.001) indirectly improves the satisfaction of football fans by improving the performance of Black Stars. The satisfaction of football fans in Ghana is linked to lack of coherence among players, perceived performance of Black Stars, call-ups and good governance.